The Critical Point in the Certification System for Project Manager in Indonesia. (2017) - Suwandi, Putri Anggi Permata; Wibowo, M. Agung; Rusdi, H.A.
Abstract: The tender evaluation in Indonesia is usually done under the basis of the qualification of expertise which is valued from 50% to 70%. The expertise is indicated in the portfolio of working experience and expertise certificates. However, one who has the same expertise certificate may have different performance in the project. This paper attempts to identify the critical point of certification in Indonesia, classify the critical point based on the source, find the most affected critical point and find the problems that can cause critical point in certification system in Indonesia. The method of this study is mixed method; meaning that the data collected are in the forms of numeric and non-numeric. The results of the study indicate that the weakest point in the certification system is in the working experience reference. The fact that the working experience reference enclosed as his portfolio does not reflect the actual experience and sometime some of them are fake that of course, it does not guarantee his competence in the project. The result shows that the score of working experience = 787; the system of validation and verification of the association = 677; the incomplete fulfilment of the applicants requirement = 636; the lack of additional information which supports the working experience reference = 320; the objectivity of the assessors = 297; and the process of interviews = 240.